Metode Fenomenologi Edmund Husserl Dalam Pendidikan Islam - Syiraz Rozaky Bimagfiranda; Aprilia Ajeng Pertiwi; Sangkot Sirait (Al-Abshor : Jurnal Pendidikan Agama Islam, 2024)
One approach in Islamic studies is the phenomenological approach, which recognizes the existence of bias in religious studies, including Islamic studies. Phenomenology, which was initiated and developed by Edmund Husserl (1859 – 1938), places the research object from the observer's point of view. By using a phenomenological approach, observers are required to suspend and undo their subjective judgments, so that observers can obtain a more objective and real picture. This research discusses Edmund Husserl's phenomenology and its relevance in the scope of Islamic studies, then places it as an approach in studying the discourse of Indonesian Islam and Progressive Islam in Indonesia. In this case, the research method used is library research. This research is qualitative research working at an analytical level and has an emic perspective, that is, obtaining data not from the researcher's perception, but based on conceptual and theoretical facts. The data obtained in this research comes from the literature. This means that the activities in this research only focus on data from the literature. The results of this research are that Husserl's phenomenological approach with phenomenological reduction, eidetic reduction and transcendental reduction does not then eliminate religious knowledge and beliefs, but rather undoes them with the aim of reflection and obtaining the real form of the object. A phenomenological approach to "religious experience" will lead to a structure of awareness about the benefits and level of human need for religious practices and perspectives. Phenomenological studies of religious phenomena will produce extensive knowledge about the truths that exist in Islam.